A review of the pathways, limitations, and perspectives of plastic waste recycling - Alrazen, Hayder A.; Aminossadati, Saiied M.; Mahmood, Hussein A.; Hussein, Ahmed Kadhim; Ahmad, Kamarul Arifin; Dol, Sharul Sham; Jabbar, Sattar; Algayyim, Sattar Jabbar Murad; Konarova, Muxina; Fattah, I. M.R. (Springer Science and Business Media Deutschland GmbH, 2025)
The valorisation of plastic waste through diverse recycling technologies offers a strategic response to the escalating global plastic crisis, combining waste reduction with resource and energy recovery. This review critically examines both conventional and emerging methods—including mechanical recycling, incineration for energy recovery, pyrolysis, gasification, hydrogenation, hydrocracking, and solvent-based treatments—focusing on their technical efficacy, environmental footprint, and economic feasibility. Mechanical recycling remains the most widely adopted method, involving collection, sorting, grinding, washing, drying, and granulation processes. However, challenges such as polymer degradation, contamination, and incompatibility among mixed plastics limit the quality and applicability of recycled products. Advanced sorting technologies, including Near-Infrared (NIR) spectroscopy, Artificial Intelligence (AI), and electrostatic separation, are increasingly employed to enhance recycling outcomes. Incineration provides energy in the form of electricity, heat, or steam while significantly reducing waste volume, yet it raises environmental concerns due to the release of toxic gases and particulates. Chemical recycling emerges as a critical pillar of the circular plastic economy, enabling the breakdown of polymers into valuable chemical feedstocks. Techniques such as pyrolysis, gasification, and hydrocracking produce valuable by-products, including char, syngas, and bio-oil. The review underscores the potential of integrating incineration with carbon capture technologies to mitigate emissions and improve sustainability. It advocates for region-specific strategies supported by comprehensive techno-economic and environmental assessments. This work provides a comparative framework to inform the selection of recycling technologies, guide policy development, and identify research priorities in advancing plastic waste valorisation.